School tracking, educational mobility and inequality in German secondary education: developments across cohorts. Issue 1 (1st January 2017) - Schindler, Steffen
ABSTRACT: Secondary education is associated with a comparatively high level of inequality in Germany. This has often been attributed to the early ability-based between-school tracking in the German school system. However, as yet there has been no empirical evaluation of the actual impact of initial track placement on social inequality in final school attainment. Since educational reforms in the 1960s increased educational mobility after track placement, it can be expected that initial track allocation has become less important for the process of secondary educational attainment and the inequalities therein. By drawing on longitudinal life-course data for different birth cohorts from the 1930s to the 1980s, this paper analyses temporal developments in the connections between track placement, educational mobility and social inequality in final school outcomes. The analyses reveal that the impact of track placement actually diminished for those cohorts exposed to the reformed school system. Instead, social inequalities in school attainment are increasingly influenced by processes of educational mobility after track allocation. Furthermore, the analyses show that developments in educational mobility have contributed more to declining inequalities in access to upper secondary education than changes of the selectivities in the transition to secondary education.